UJI ANTI MIKROBA EKSTRAK AKAR SOM JAWA (Tanilum paniculatum, Jacq. (Gaertn)) - Sartini, Sartini; Usman, Muhammad (Program Studi Biologi, Fakultas Biologi Universitas Medan Area, 2014)
Antimicrobial test was conducted on plant root extract som jawa (Talinum paniculatum, jacq. (Gaertn)). Five hundred gram simplicia of som jawa root was macerated using methanol and n-heksana, and coagulated. The screening of extract methanol and n-heksana was done to get metabolic secunder; flavonoid, alkaloid, terpenoid, and saponin. The result of phytochemistry secreening test to extract methanol to metabolic secunder was negative. Antimicrobial test result showed that the extract of som jawa rootÂ is active againts microbes E.coli. Measurement is based on the test zone diameter of the clear zone generated, where . coli has the highest diameter of the clear zone compared with the others microbes such as Staphylococus aureus, Bacillus sp, Serratia sp, and Candida albicans. The values of the clear zone of each microbeÂ in order are 1,1 cm, 1 cm, 0,95cm, and 0,9 cm. These value were obtain at a concentration of 10%.